2004
DOI: 10.1243/095440704773599944
|View full text |Cite
|
Sign up to set email alerts
|

Engine performance and emissions of a compression ignition engine operating on the diesel-methanol blends

Abstract: A stabilized diesel-methanol blend was realized and a study on the performance and emissions of the diesel-methanol blend was carried out in a compression ignition engine. The study showed that the engine thermal efficiency increases and the diesel equivalent b.s.f.c. decreases with increase in the oxygen mass fraction (or methanol mass fraction) of the diesel-methanol blends due to an increased fraction of premixed combustion phase, oxygen enrichment and improvement in the diffusive combustion phase. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 11 publications
1
58
0
Order By: Relevance
“…In order to make this successful, many researchers have started to use methanol blends with diesel fuel to lessen the air pollution and also as an alternative fuel to replace mineral diesel. Previous research by Huang et al (2004) shows that increased methanol content in the diesel-methanol mixture reduces smoke, CO and THC emissions but on the other hand increases NO x emissions. However, during combustion, gaseous and particulate matter exhausted from the diesel engine results in air pollution.…”
Section: Introductionmentioning
confidence: 91%
“…In order to make this successful, many researchers have started to use methanol blends with diesel fuel to lessen the air pollution and also as an alternative fuel to replace mineral diesel. Previous research by Huang et al (2004) shows that increased methanol content in the diesel-methanol mixture reduces smoke, CO and THC emissions but on the other hand increases NO x emissions. However, during combustion, gaseous and particulate matter exhausted from the diesel engine results in air pollution.…”
Section: Introductionmentioning
confidence: 91%
“…Properties of palm stearin biodiesel have been measured by National Test House, Kolkata, and those values are being used directly for experimental as well as numerical works. Properties of ethanol, methanol and conventional petro diesel are taken from the previous works of Sayin (2010), Huang et al (2004b) and Shi et al (2006). Some of the important properties of the above-said four fuels have been listed in Table 1 for comparison.…”
Section: Properties Of Fuelmentioning
confidence: 99%
“…Quite a few studies suggested that addition of alcohol could further reduce the particulate matter (PM) emission. Also, the addition of ethanol and methanol to diesel/biodiesel improves the cold flow properties of the fuel blends (Chao et al 2001;Huang et al 2004b). A few number of experimental studies have also been carried out by adding ethanol and methanol to diesel and biodiesel blends.…”
Section: Introductionmentioning
confidence: 99%
“…Fumigation mode and Emulsion mode. A separate fuel injector used to fumigate methanol with the inlet air in fumigation mode and in emulsion mode, an additive should be used to maintain stability of the mixture because of the poor miscibility of diesel -methanol blend [6,7]. Alternatively, a fuel injector can be utilized to introduce methanol in the combustion chamber [8,9].…”
Section: Introductionmentioning
confidence: 99%